2005
DOI: 10.1016/j.jacc.2005.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Monitored Atrial Fibrillation Duration Predicts Arterial Embolic Events in Patients Suffering From Bradycardia and Atrial Fibrillation Implanted With Antitachycardia Pacemakers

Abstract: In a cohort of patients with bradycardia and AF, arterial embolism was common in patients with ischemic cardiopathy, hypertension, diabetes mellitus, and in patients with known stroke risk factors. Atrial fibrillation occurrences longer than one day were independently associated with embolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
238
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(259 citation statements)
references
References 36 publications
(26 reference statements)
5
238
0
6
Order By: Relevance
“…[1][2][3][4][5][6] However, the characteristics of AF retrieved from pacemaker interrogation, in particular its duration, may differ from those derived from clinical observations. Recent advancement of pacemaker algorithms for the prevention of atrial tachycardias, fibrillation and flutter (AT/AF) with atrial overdrive pacing (AOP) has been expected to reduce the incidence of AT/AF, though the effectiveness of these preventive algorithms is still controversial.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] However, the characteristics of AF retrieved from pacemaker interrogation, in particular its duration, may differ from those derived from clinical observations. Recent advancement of pacemaker algorithms for the prevention of atrial tachycardias, fibrillation and flutter (AT/AF) with atrial overdrive pacing (AOP) has been expected to reduce the incidence of AT/AF, though the effectiveness of these preventive algorithms is still controversial.…”
mentioning
confidence: 99%
“…Capucci et al found that the risk of TE, adjusted for known risk factors, increased by 3.1 times in patients with devicedetected AF episodes longer than 1 day during follow-up. 11 Our data showed that patients with persistent AF were 9.8 times more likely to have TE events during the perioperative period. One reason for the high risk of TE may be that anticoagulation with warfarin was discontinued or even not previously prescribed before the procedure in those patients with a history of AF or previous stroke.…”
Section: Discussionmentioning
confidence: 49%
“…3,11 Furthermore, persistent AF was the only independent risk factor for perioperative TE events. However, pacing modes were not found to be a risk factor for TE events during the perioperative period in our study population.…”
Section: Discussionmentioning
confidence: 96%
“…23 In contrast, another study looking at the duration of atrial high rate events, found that only episodes lasting longer than one day increased risk. 27 The investigators also noted that 12% of the cohort received an ICD shock during the first 3 months after implantation. Occurrence of a shock was associated with an increase in hospitalization for CHF and for subsequent shocks, but not death.…”
Section: As Submitted Tomentioning
confidence: 98%